Safety and effect of high dose allopurinol in patients with severe left ventricular systolic dysfunction - Ansari-Ramandi, Mohammad Mostafa (J Cardiovasc Thorac Res, 2017)
Introduction: Allopurinol used in the treatment of gout has been shown to improve the vascular endothelial dysfunction and reduce the dysfunction of the failing heart. This study was done to evaluate the effect and safety of allopurinol in non-hyperuricemic patients with chronic severe left ventricular (LV) dysfunction. Methods: In this study, 35 consecutive cases of non-hyperuricemic patients with chronic heart failure who had severe LV systolic dysfunction (ejection fraction of less than 35%) and were on optimal guideline directed medical therapies for at least 3 months were included. Allopurinol was administered with the dose of 300 mg po daily for 1 week and then it was up-titrated to a dose of 600 mg po daily for 3 months. Six minute walk test, strain imaging, laboratory testing were done for every patient at baseline and after 3 months treatment with allopurinol. Results: In this study 30 heart failure (HF) patients with a mean age of 49.3 ± 14.4 years old were evaluated. No adverse effects were reported except for one case of skin rash after 4 days treatment which was excluded from the study. Study showed significant improvement of six minute walk test of the patients from 384.5 ± 81.5 meters to 402.8 ± 89.6 meters and the global longitudinal peak strain (P < 0.001). There was also significant decrease in the level of erythrocyte sedimentation rate and N-terminal pro-brain natriuretic peptide (NT-proBNP) after 3 months. Conclusion: Allopurinol could be of benefit in non-hyperuricemic patients with severe LV systolic dysfunction without significant adverse effects. Randomized clinical trials are needed in future to confirm the results.